Politik Seksualitas Dan Keberadaan LGBT Di Indonesia Terhadap Kebijakan Negara - Intan Kurnia Syaputri; Robeet Thadi; Adisel Adisel (JOPPAS: Journal of Public Policy and Administration Silampari, 2020)
ABSTRACT The purpose of this study is to discuss the meaning of sex and gender orientation is for LGBT, to analyze it the discourse of Foucault and Freud's sexuality, then whether countries have provided a sense of security and social security relating to the identity of LGBT people. Indonesian people tend to have homophobic attitudes towards LGBT. This discriminatory attitude from the community comes because of insufficient language to interpret one's gender identity. The language that is mastered by Indonesian people are binary, male or female, if it is not included in the grouping it will be considered abnormal as LGBT gender identity. This research method by analyzing the literature that the author summarizes and uses the discourse of Foucault and Freud's sexuality. The results of this study that LGBT still experience discrimination in the community, while the Constitution is not yet able to protect the problem of discrimination. The conclusions from the results of the analysis and a collection of several research results which the author summarizes, clearly say that Indonesia is a country that does not protect and does not guarantee the rights of LGBT people. Keywords: LGBT, Politics of Sexuality, State Policy.